Fiat Money Inconsistency and the Return of Dinar-Dirham as a Medium of Exchange in the Community - Chairul Iksan Burhanuddin; M Hidayat (Universitas Muhammadiyah Sorong, 2021)
Coronavirus ior ireferred ito ias icovid-19 ihas icaused ivarious ikinds iof inegative ieffects, iespecially iin ithe ieconomic ifield. iThe isoaring iunemployment irate, ithe icontraction iin ithe ivalue iof ithe irupiah iand iother icurrencies ihas iresulted iin ian iincreasingly isluggish ieconomic imovement iin irecent itimes iuntil ithe ipanic iof ithe ivalue iof igold icontinues ito irise iin irecent imonths. iThe iqualitative imethod iis iused iby iscientifically idescribing ithe iimpact iof ithe iCovid i19 ivirus icase ion ithe imovement iof icurrency iand igold ivalues. iThe iresults iof ithis istudy iindicate ithat ithe iCovid i19 ivirus ihas ia iquite inegative iimpact ion ithe ieconomic isector, iespecially ion icurrency iand igold ivalue imovements. iThe imovement iin ithe ivalue iof ithe irupiah icontracted ito itouch iRp.14,000 iwhile ithe ivalue iof igold itended ito irise isignificantly. iThe irising igold ivalue ishows ia ipositive itrend itowards ithe ipossible iimplementation iof ithe ilegal iuse iof ithe idinar iand idirham icurrency iin ithe icommunity. iGold iis ino ilonger iseen ias ia iSave iHaven, ibut iits irole ias ian iextension iof imuamalah iactivities i(buying iand iselling) iin ithe icommunity iis iincreasingly ivisible. iThere iis ipanic iand ipsychologically idisturbing ieconomic iand icommunity iactors iin iresponding ito ithis iincident.iCoronavirus ior ireferred ito ias icovid-19 ihas icaused ivarious ikinds iof inegative ieffects, iespecially iin ithe ieconomic ifield. iThe isoaring iunemployment irate, ithe icontraction iin ithe ivalue iof ithe irupiah iand iother icurrencies ihas iresulted iin ian iincreasingly isluggish ieconomic imovement iin irecent itimes iuntil ithe ipanic iof ithe ivalue iof igold icontinues ito irise iin irecent imonths. iThe iqualitative imethod iis iused iby iscientifically idescribing ithe iimpact iof ithe iCovid i19 ivirus icase ion ithe imovement iof icurrency iand igold ivalues. iThe iresults iof ithis istudy iindicate ithat ithe iCovid i19 ivirus ihas ia iquite inegative iimpact ion ithe ieconomic isector, iespecially ion icurrency iand igold ivalue imovements. iThe imovement iin ithe ivalue iof ithe irupiah icontracted ito itouch iRp.14,000 iwhile ithe ivalue iof igold